Tecnologic Development on Pleurotus Cultivation: Specific Practices Used in Brazil - Albertia, Maria Melisa; Oliveira Cunha, Matheus Luis [UNESP]; Mendes, Danilo Wanderley [UNESP]; Vieira Junior, Wagner Goncalves [UNESP]; Zied, Diego Cunha [UNESP] (Inst Tecnologia Parana, 2021)
In Brazil, Pleurotus is the most important mushroom produced especially P. ostreatus var. Florida. In this country as in many others, the great potential for mushroom cultivation remains unexplored. Therefore, it is very important to develop new studies that allow optimizing its production. The aims of the manuscript were: i) to evaluate the productivity of six different species of Pleurotus ( P. citrinopileatus; P. djamor; P. ostreatus; P. ostreatus var. Florida; P. pulmonarius; P. sapidus); ii) to measure the effect of three different environmental conditions during cultivation of three isolates of P. ostreatus var. Florida. As results, P. ostreatus and P. sapidus were the most productive isolates under the evaluated conditions. Different environments produced variable effects according to the P. ostreatus var. Florida isolates, being possible to observe a highly plastic strain (POF 02/18), a highly sensitive strain (POF 03/18) and a strain with variable responses (POF 01/18).Y
Keywords: Oyster mushrooms; edible mushrooms; food production; bioconversion; agro-industrial wastes